Maternal Risk Factors for Autism Spectrum Disorder - Noor Abdulmohsin Mohammed; Najdat Sh. Mahmood; Jalil I. Alezzi; Bassim Mohammed Ahmed; Mohamed Aydaroos Aljefri (Diyala Journal of Medicine)
Background: Autism Spectrum Disorder (ASD) is a complex neurodevelopmental disorder characterized by deficits in social communication, restricted interests, and repetitive behaviors. The etiology of ASD is multifactorial, involving genetic, environmental, and maternal factors. Recent studies have suggested maternal factors, such as advanced maternal age, high BMI, smoking, and depression during pregnancy, as significant risk factors for ASD.